Looking Inside The Skyscraper: Size and Occupancy of Toronto Office Buildings, 1890-1950 - Gad, Gunter; Holdsworth, Deryck (Urban History Review / Revue d'histoire urbaine, 1987)
Although the emergence of skyscrapers as a distinctive element in the downtown fabric symbolizes economic change and progress, research questions surrounding their appearance need to go beyond merely noting their height and facade detail. Using case studies in Toronto, Ontario, this paper investigates more useful measures such as floor space, tenancies, and employment levels that have been calculated for several generations of office buildings. The possibilities and limitations of fire insurance atlases, assessment rolls, street directories, and company records are examined. The case studies suggest the interrelatedness of forces at work in shaping office-district landscapes.